Attitudes and Beliefs Toward Computerized Cognitive Training in the General Population - Goghari, Vina M.; Krzyzanowski, Daniel; Yoon, Sharon; Dai, Yanni; Toews, Deanna (Frontiers in Psychology, 2020)
Introduction: In recent years, computerized cognitive training programs have been developed commercially for widespread public consumption. Despite early enthusiasm, whether these programs enhance cognitive abilities in healthy adults is a contentious area of investigation. Given the mixed findings in the literature, researchers are beginning to investigate how beliefs and attitudes towards cognitive training impact motivation, expectations, and gains after cognitive training. Method: We collected survey data from 497 North American participants from Amazon’s Mechanical Turk (MTurk). This survey asked novel questions regarding respondents’ beliefs about the effectiveness of cognitive training for improving different domains of cognition, mood, and daily life; beliefs about whether computerized cognitive training programs are supported by research; and whether impressions of cognitive training have improved or worsened over time. Results: Almost half of the surveyed participants had used computerized cognitive training, and respondents with a self-reported psychological or neurological disorder were more likely to have used cognitive training platforms than participants without such conditions. Motivations for using cognitive training included curiosity; to improve or maintain cognition; to prevent cognitive decline; and/or for enjoyment or fun. Participants believed that computerized cognitive training is somewhat effective for improving mood and cognition across a variety of domains. Greater age and fewer years of education predicted perceived effectiveness of computerized cognitive training. Finally, participants largely reported unchanged opinions of cognitive training platforms over time. Conclusions: Our study suggests the need for future research regarding the general population’s beliefs and attitudes towards computerized cognitive training, along with knowledge translation for relevant stakeholders.